Association of Periodontal Destruction and Diabetes with Mortality. (January 2017) - Kebede, T.G.; Holtfreter, B.; Kocher, T.; Meisel, P.; Dietrich, T.; Biffar, R.; Dörr, M.; Völzke, H.; Pink, C.
Current evidence indicates the effects of periodontitis on diabetes as well as mortality, for which diabetes itself represents a risk factor. However, the possible interaction of these 2 chronic conditions regarding mortality has not yet been investigated. Therefore, the purpose of this study was to evaluate whether periodontal destruction interacts with diabetes on all-cause and cardiovascular disease (CVD) mortality or if diabetes serves as a mediator in this association. The study sample comprised 3, 327 participants aged 20 to 81 y from the Study of Health in Pomerania. Periodontal destruction was assessed via clinical attachment level (CAL) and the number of missing teeth. Information on mortality (date and ICD-10 code) was ascertained from death certificates. Directed acyclic graphs were used to identify potential confounders, and Cox proportional hazard models were applied. In 36, 701 person-years of follow-up, 263 study participants deceased, 89 due to CVD. Fully adjusted main effect models resulted in hazard ratios of 1.01 (95% confidence interval [95% CI]: 1.002 to 1.01) for extent of CAL ≥3 mm, 1.10 (95% CI: 1.03 to 1.18) for mean CAL, and 1.03 (95% CI: 1.01 to 1.04) for the number of missing teeth regarding all-cause mortality. Analogous results were obtained for CVD mortality, with hazard ratios of 1.01 (95% CI: 0.99 to 1.02), 1.10 (95% CI: 0.98 to 1.23), and 1.02 (95% CI: 0.99 to 1.05) for extent of CAL, mean CAL, and the number of missing teeth, respectively. Findings did not indicate additive interaction of periodontal destruction and diabetes regarding all-cause and CVD mortality. Similarly, no substantial evidence was found to demonstrate the presence of multiplicative interaction or mediation. Besides adjustment for baseline covariates, time-varying covariates were also considered and led to comparable results. In summary, despite their reciprocal relationship, periodontal destruction and diabetes may be independent risk factors for all-cause and CVD mortality.